HUBUNGAN ANTARA BURNOUT AKADEMIK DENGAN PRESTASI BELAJAR SISWA DI SDN 57 SINGKAWANG - Gelsy Chania; Rini Setyowati; Kamaruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to: 1) Describe the level of academic burnout among students at SDN 57 Singkawang, 2) Describe the level of academic achievement among students at SDN 57 Singkawang, 3) Analyze the relationship between academic burnout and academic achievement among students at SDN 57 Singkawang. This study employs a quantitative correlational method with an associative research design. The population consists of 41 students from grades IV, V, and VI at SDN 57 Singkawang. The sampling technique used is total sampling, with the sample comprising 41 students from grades IV, V, and VI at SDN 57 Singkawang. Data collection techniques include a questionnaire burnout and document study. Data analysis techniques include overall averages and Pearson product-moment correlation. The results of the study indicate that: 1) Academic burnout among students is at a moderate level, with an overall average of 48.11, 2) Academic achievement in the cognitive domain is at a low level, with an overall average of 54.09, 3) There is a significant relationship between academic burnout and academic achievement at SDN 57 Singkawang, with a coefficient of determination of 25.60%. The significance value is 0.001, and the calculated Pearson Correlation (t-value) is -0.506.